Energy and exergy analyses of a steam reforming process for hydrogen production - Dilmac, Omer Faruk; Ozkan, Semra K. (INDERSCIENCE ENTERPRISES LTD, 2008)
Hydrocarbon steam reforming is an important process for hydrogen production. In petroleum refineries, steam reforming is most commonly used for hydrogen production from naphtha and light hydrocarbon gases (methane, ethane and propane). Since the hydrocarbon steam reforming system is one of the highest energy intensive systems in a petroleum refinery it should be directed to a more efficient use of energy through better process design and analysis, based on accurate thermodynamic analysis via applications of the first and second laws of thermodynamics, and thus, applications of exergy concept. The purpose of this study is to perform the energy and exergy analyses of a natural gas steam reforming process presently in operation at TUPRAS refinery in (I) over dot zmit, Turkey, The energy and exergy efficiencies of the steam reformer were found to be 94.33% and 78.23%, respectively, and the lowest exergy efficiency was obtained as 66.81% for steam generator.
Keywords: energy analysis; exergy analysis; hydrogen production; steam reforming; Thermodynamics; Energy & Fuels